Spanish shrimp (Pandalus borealis) fishery in Flemish Cap in 1997. - Junquera, Susana; Bóveda-González; María del Carmen Eulalia; Álvarez-Pérez, María Soledad; Río-Iglesias, José Luis del (1997)
In 1997 one Spanish trawler have been involved in the shrimp fishery in Flemish Cap (NAFO Div. 3M) from March to May. A scientific observer remained on board this trawler during all the fishing period, providing information on the fishing activity and carrying out biological sampling. The gear used was a twin trawl, with a 19 mm bar spacing sorting grate. In this paper, the main results of this fishery are presented.